Analysis and behaviour of bioactive pollutants in wastewater and reuse for irrigation: addressing country specific issues in Mexico and the UK - Garduno Jimenez, Andrea Lorena (2021)
Treated and untreated municipal wastewater reuse for agricultural irrigation is a widespread worldwide practice that has many benefits. These include reusing a waste stream, its year-round availability and the presence of nutrients in wastewater. However, municipal wastewater has been identified as one of the main sources of bioactive chemical pollutants or BACs (also known as emerging pollutants) in the environment. Many unknowns remain in terms of the extent of the removal of these pollutants using conventional wastewater treatment, seasonal and geographical variation on the prevalence of these pollutants, the extent of natural attenuation and the behaviour of these pollutants once in the environment. The aim of this thesis was to address some of these knowledge gaps by developing environmentally-relevant targeted and untargeted analytical methods, modelling tools, and undertaking an evaluation of wastewater treatment plants and the aquatic environment in the UK and Mexico.